Students' perception of teacher's strategies in teaching reading - Islamiyah, Kharismatul; Ni’mah, Fauziyatun (Jurnal Langua, 2024)
This research is motivated by the importance of students' English reading skills. However, not all students have the ability to read English well. In terms of perception, students can have individual feelings and opinions. Students should have their perception of which strategy is more effective and interesting that teachers use for reading skills. In reading learning, students prefer to use interesting and interactive strategies. This research was conducted to find out how students perceive the strategy used by teachers. The sample of this research was a tenth grader of 22 students at MA Ma’arif Miftahul Ulum Melirang. The design of the research is qualitative descriptive and uses the instruments of questionnaires and interviews. The results of the research are described in the form of pie charts and descriptions. The research concluded that the strategies used by teachers can help students develop their reading skills. Besides, students also agreed and liked the strategy used which made most students feel interested, comfortable, and more active in following reading learning. Overall it was found that many of them expressed a positive response to the strategies used by teachers in learning